NEUTRON DIFFRACTION APPLIED TO GEOLOGICAL TEXTURE AND STRESS ANALYSIS - Schäfer W. (My University, 2002)
Texture is defined as preferred crystallographic orientation in a polycrystalline aggregate. The main mechanisms of geological texture formation are crystallization, sedimentation, plastic deformation, recrystallization and metamorphism. Textures of geomaterials are fingerprints of the earth's history. The complexity of geological texture analysis results mainly from the overprinting of different textures on several mineral components during different orogenic periods. Quantitative texture analysis, i.e., the calculation of a three-dimensional orientation distribution function of crystallites, is based on experimental pole figures which represent the orientation distributions of certain crystallographic directions and which can be obtained from X-ray or neutron-diffraction techniques. Due to the high penetration capability of neutrons, large specimens can be investigated resulting in global volume textures rather than local surface textures from X-rays. Neutron-diffraction pole figures are characterized by high grain statistics even on coarse-grained material. Individual pole figures can also be obtained from reflection-rich diffraction patterns of multiphase rocks and low-symmetry mineral constituents by using position-sensitive detectors and by pattern decomposition by means of profile-fitting methods. Neutron texture diffractometers are operated in the constant-wavelength mode at steady-state sources and using time-of-flight techniques at pulsed sources. Different experimental set-ups are discussed. Results of neutron-diffraction texture analyses on monomineralic and polymineralic rocks are presented, e.g, on calcite, quartzite, plagioclase, pyrrhotite ores, granite, and orthopyroxone-sillimanite-granulite. The wide application spectrum of neutron texture analysis includes objects of the outer solar system as in the low-temperature texture study on ice and the non-destructive investigations on rare pieces of meteorites. The application of neutron diffraction on strain measurements and residual stress analysis of geological material is discussed. Natural effects on rocks are orders of magnitude smaller than in technological material and drilling gives rise to stress relaxation. Experimental deformations can be observed during in situ measurements at various pressures and temperatures. Neutron strain diffractometers are described. Examples of recent results on the full strain/stress tensor in sandstone and on strain partitioning in polymineralic rocks are given. Future prospects of new high-intensity neutron sources are promising in performing combined structure, texture and stress analysis. New instruments are under construction and software packages on the basis of full-pattern Rietveld refinements are available.